Targeting human plasmacytoid dendritic cells through BDCA2 prevents skin inflammation and fibrosis in a novel xenotransplant mouse model of scleroderma - Ross, Rebecca L.; Corinaldesi, Clarissa; Migneco, Gemma; Carr, Ian M.; Antanaviciute, Agne; Wasson, Christopher W.; Carriero, Antonio; Distler, Jörg; Holmes, Steve; El-Sherbiny, Yasser M.; McKimmie, Clive S.; Del Galdo, Francesco (Annals of the Rheumatic Diseases, 2021)
Plasmacytoid dendritic cells (pDC) have been implicated in the pathogenesis of autoimmune diseases, such as scleroderma (SSc). However, this has been derived from indirect evidence usingex vivohuman samples or mouse pDCin vivo. We have developed human-specific pDC models to directly identify their role in inflammation and fibrosis, as well as attenuation of pDC function with BDCA2-targeting to determine its therapeutic application. RNAseq of human pDC with TLR9 agonist ODN2216 and humanised monoclonal BDCA2 antibody, CBS004. Organotypic skin rafts consisting of fibroblasts and keratinocytes were stimulated with supernatant from TLR9-stimulated pDC and with CBS004. Human pDC were xenotransplanted into Nonobese diabetic/severe combined immunodeficiency (NOD SCID) mice treated with Aldara (inflammatory model), or bleomycin (fibrotic model) with CBS004 or human IgG control. Skin punch biopsies were used to assess gene and protein expression. RNAseq shows TLR9-induced activation of human pDC goes beyond type I interferon (IFN) secretion, which is functionally inactivated by BDCA2-targeting. Consistent with these findings, we show that BDCA2-targeting of pDC can completely suppressin vitroskin IFN-induced response. Most importantly, xenotransplantation of human pDC significantly increasedin vivoskin IFN-induced response to TLR agonist and strongly enhanced fibrotic and immune response to bleomycin compared with controls. In these contexts, BDCA2-targeting suppressed human pDC-specific pathological responses. Our data indicate that human pDC play a key role in inflammation and immune-driven skin fibrosis, which can be effectively blocked by BDCA2-targeting, providing direct evidence supporting the development of attenuation of pDC function as a therapeutic application for SSc.
CRIS-Team Scopus Importer:2021-06-25
Keywords: autoimmune diseases; inflammation; scleroderma; systemic